Investigation on influence of SiCp on three-body abrasive wear behaviour of glass/epoxy composites - Ajith G. Joshi; S. Basavarajappa; S. Ellangovan; B.M. Jayakumar (Fracture and Structural Integrity)
The study presents the influence of SiCp incorporation on three-body abrasive wear behaviour of glass/epoxy composites. The investigation was carried out using dry sand rubber wheel abrasive wear test apparatus. 2k factorial design of experiments was used to capture the experimental data. The parameters considered are abrading distance, load and speed. The wear rate was found to increase with the increasing values of wear parameters. The applied load has exhibited significant effect on wear rate. Incorporation of SiCp contributed to enhance wear resistance of glass/epoxy composites. The linear regression was also presented in the study to correlate abrasion parameters with wear rate. SEM image analysis of abraded surface revealed the occurrence of ploughing, micro-cutting, matrix removal and fiber breakage.